Outcomes of the Conversion of the Fontan-Kreutzer Operation to a Total Cavopulmonary Connection for the Failing Univentricular Circulation - Fernandes,Gabriel Carmona (2019)
Abstract Background: The Fontan-Kreutzer procedure (FK) was widely performed in the past, but in the long-term generated many complications resulting in univentricular circulation failure. The conversion to total cavopulmonary connection (TCPC) is one of the options for treatment. Objective: To evaluate the results of conversion from FK to TCPC. Methods: A retrospective review of medical records for patients who underwent the conversion of FK to TCPC in the period of 1985 to 2016. Significance p < 0,05. Results: Fontan-type operations were performed in 420 patients during this period: TCPC was performed in 320, lateral tunnel technique in 82, and FK in 18. Ten cases from the FK group were elected to conversion to TCPC. All patients submitted to Fontan Conversion were included in this study. In nine patients the indication was due to uncontrolled arrhythmia and in one, due to protein-losing enteropathy. Death was observed in the first two cases. The average intensive care unit (ICU) length of stay (LOS) was 13 days, and the average hospital LOS was 37 days. A functional class by New York Heart Association (NYHA) improvement was observed in 80% of the patients in NYHA I or II. Fifty-seven percent of conversions due to arrhythmias had improvement of arrhythmias; four cases are cured. Conclusions: The conversion is a complex procedure and requires an experienced tertiary hospital to be performed. The conversion has improved the NYHA functional class despite an unsatisfactory resolution of the arrhythmia.